The holistic view of urban space method: Examination of public spaces around Kadıköy Marmaray stations - Ozbudak, Ozgun; Barkul, Omur (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
This study focuses on the development of a 7-criteria examination method for understanding, analyzing, mapping, and interpreting urban space, and the testing of the method in the area around Marmaray Kadikoy stations. Within the framework of the study, based on the need for a method that enables the understanding and analysis of urban space, 7 research criteria were created that include the holistic data of the city. These criteria aim to obtain holistic data by combining the plan level and urban form data of the urban space, the three-dimensional perceived (experienced) data of the space, the relationship of the historical process with economic, political, social, and spatial dynamics, and mapping techniques. This method, called the holistic view of urban space, allows data to be brought together, mapped, and multiple readings and inferences to be made while experiencing and researching urban space. In the study, carried out with the qualitative research method, theoretical information is brought together with the thematic analysis method and associated on the matrix. By associating the concepts on the matrix, the holistic view of urban space method is obtained. The data obtained after the field examination are analyzed with 7 examination criteria, and a mapping study is carried out. The analysis criteria make it possible to collect data at eye level and at plan level and to interpret them by associating them in the analysis of the urban space. The criteria allow deepening the information by elaborating the collected data, as well as providing holistic information from a higher scale through induction.
Keywords: Kadikoy; Marmaray; public space; public space analysis; public space analysis method; station squares; urban space; Architecture